Phenolic composition and extraction methods of Brazilian fruits: jabuticaba (Plinia spp.), açaí (Euterpe oleraceae Mart.), jussara (Euterpe edulis Mart.) and cocoa (Theobroma cacao L.) (Research, Society and Development, 2022)
Brazil is well known for its great botanic diversity. The native fruits species of jabuticaba (Plinia spp.) açaí (Euterpe oleraceae Mart.), jussara (Euterpe edulis Mart.), and cocoa (Theobroma cacao L.) stand out because of their high antioxidant capacity and diverse phenolic composition, which are the subject of several studies aiming for the extraction of phenolic fractions for their characterization and applicability. This review aimed to discuss the main phenolics identified in these four plant species, and an overview of the most recent methods of phenolic compounds extraction from these species. This work can contribute to future research projects, helping researchers to reach efficient methods of extraction.